A Formative Assessment Observation Protocol to Measure Implementation: Evaluating the Scoring Inference. Issue 4 (1st October 2020) - Lyon, Christine J.; Nabors Oláh, Leslie; Brenneman, Meghan
ABSTRACT: There is currently a lack of instrumentation with sufficient technical quality focused on the implementation of classroom formative assessment at a grain-size appropriate for the provision of feedback to teachers and program developers. This paper details the development of a validity argument for the High-Impact Classroom Assessment Practices observation protocol (HI-CAP), and examines how to begin evaluating one inference in the interpretative argument. We present a conceptual framework for the HI-CAP and then articulate the interpretive argument. Finally we present evidence to evaluate one part of this argument, the scoring inference, using independent ratings of lessons from pairs of observers across 65 lessons in ninth-grade ELA and mathematics which suggest modest evidence for appropriateness, consistency, and preliminary evidence supporting the scoring model. We conclude with a discussion of the strengths and limitations of the current protocol and training procedures and implications for developing a validity argument for other similar protocols.